CARBOTHERMIC REDUCTION OF ELECTRIC ARC FURNACE DUST AND CALCINATION OF WAELZ OXIDE BY SEMI-PILOT SCALE ROTARY FURNACE - (:unkn) unknown (TECHNICAL FACULTY, BOR-SERBIA, 2012)
The paper gives a common outline about the known recycling techniques from electric arc furnace dusts and describes an investigation of a pyrometallurgical process for the recovery of zinc and iron from electric arc furnace dusts (EAFD). In the waelz process, the reduction of zinc and iron from the waste oxides using solid carbon (lignite coal) was studied. In the reduction experiments; temperature, time and charge type (powder and pellet) were investigated in detail. It was demonstrated that zinc and iron recovery (%) increases with increasing temperature as well as time. Pelletizing was found to be a better method than using the powder as received for the zinc recovery and iron conversion (Fe3+ -> Fe degrees). In the calcination (roasting) process, crude zinc oxide, which evaporated from non-ferric metals were collected as condensed product (crude waelz oxide), was heated in air atmosphere. Lead, cadmium as well as chlorine and other impurities were successfully removed from crude waelz oxide by this method. In the calcination experiments; temperature and time are investigated in detail. It was demonstrated that zinc purification (%) increases with increasing temperature. The highest zinc refining (%) was obtained at 1200 degrees C for 120 minutes. A kinetic study was also undertaken to determine the activation energy of the process. Activation energies were 242.77 kJ/mol for the zinc recovery with powder forms, 261.99 kJ/mol for the zinc recovery with pellet forms respectively. It was found that, initially, the reaction was chemically controlled.
Keywords: Zinc; Zinc oxide; Iron oxide; Waste mixed oxides; Pyrometallurgy; ZINC; RECOVERY; LEAD